2016
DOI: 10.1097/qai.0000000000001070
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Specific miRNA Profile in HIV-Exposed Seronegative Individuals

Abstract: Our studies demonstrate that HIV-1 exposure modifies miRNAs expression even in the absence of productive infection. Because those miRNAs that are specifically increased only in HESN have been known to reduce HIV-1 replication, their modulation could represent an important mechanism in resistance to HIV-1 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Another interesting phenotype in HIV infection resistance is HIV-exposed seronegative individuals (HESN), highly virus-exposed individuals persistently seronegative. The expression profile of 84 miRNA of these patients has been assessed in unstimulated PBMC of HESN, HIV+ individuals, and healthy controls [75]. Interestingly, miR-99a is also upregulated in HESN as we reported in our LTNP.…”
Section: Discussionsupporting
confidence: 55%
“…Another interesting phenotype in HIV infection resistance is HIV-exposed seronegative individuals (HESN), highly virus-exposed individuals persistently seronegative. The expression profile of 84 miRNA of these patients has been assessed in unstimulated PBMC of HESN, HIV+ individuals, and healthy controls [75]. Interestingly, miR-99a is also upregulated in HESN as we reported in our LTNP.…”
Section: Discussionsupporting
confidence: 55%
“…These data suggest that the IL-21/miR-29 axis contributes to the control of HIV-1 replication and could be exploited in the design of new therapeutic strategies. Consistently with this observation, we recently showed that miR-29 is highly expressed in plasma and peripheral blood mononuclear cells (PBMCs) of HIV-1 exposed seronegative individuals (HESN), suggesting a role of this miRNA in the natural resistance to HIV-1 infection [19]. Based on these premises we performed an in-depth analysis of the possible role played by the IL-21/miR-29 axis in the natural resistance to HIV-1 infection observed in HESN.…”
Section: Introductionsupporting
confidence: 66%
“…Second, IL-21 triggers antiviral humoral response by enhancing B cell functions in both chronically SIV-infected rhesus macaques [27] and humans [2,[28][29][30]. Third, IL-21 elicits the STAT3dependent expression of miR-29 [13], a miRNA family which plays a crucial role in thwarting HIV-1 replication [15] and whose expression is significantly augmented in HESN PBMCs [19]. In our experimental setting, no significant difference were detected in perforin and granzyme expression in any of the analysed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although all three theories may be correct there is increasing evidence that ex-miRNA are functional, can be passed between leukocytes in vitro and in vivo , and play a role in disease ( 161 164 ). Supporting a functional role is the finding that, miR-233 and miR-29a are upregulated in the serum, and unstimulated PBMCs of HIV-exposed seronegative individuals (HESN) compared with healthy controls ( 165 ). PBMCs from HESN individuals release greater amounts of miR-223 and miR-29a when infected with HIV in vitro and infection is also better controlled, prompting the study’s authors to speculate that miR-223 and miR-29a could represent novel therapeutic targets.…”
Section: Extracellular Mirnas and Host Response To Pathogensmentioning
confidence: 99%